2009
DOI: 10.1128/jb.00325-09
|View full text |Cite
|
Sign up to set email alerts
|

Optical Mapping Reveals a Large Genetic Inversion between Two Methicillin-Resistant Staphylococcus aureus Strains

Abstract: Staphylococcus aureus is a highly versatile and evolving bacterium of great clinical importance. S. aureus can evolve by acquiring single nucleotide polymorphisms and mobile genetic elements and by recombination events. Identification and location of novel genomic elements in a bacterial genome are not straightforward, unless the whole genome is sequenced. Optical mapping is a new tool that creates a high-resolution, in situ ordered restriction map of a bacterial genome. These maps can be used to determine gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…In fact, it has been shown that Whole Genome Mapping could be routinely used as an aid to bacterial genome sequence assembly (11) and closure of sequence gaps (31). Using comparative whole-genome mapping, we (24) have also shown the presence of a large genetic inversion event in a methicillin-resistant S. aureus (MRSA). Using Salmonella enterica serovar Typhimurium isolates from an outbreak, Saunders et al (21) have shown that their WGMs distinguished variation in genome maps associated with microbial resistance and its prophage content.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…In fact, it has been shown that Whole Genome Mapping could be routinely used as an aid to bacterial genome sequence assembly (11) and closure of sequence gaps (31). Using comparative whole-genome mapping, we (24) have also shown the presence of a large genetic inversion event in a methicillin-resistant S. aureus (MRSA). Using Salmonella enterica serovar Typhimurium isolates from an outbreak, Saunders et al (21) have shown that their WGMs distinguished variation in genome maps associated with microbial resistance and its prophage content.…”
Section: Discussionmentioning
confidence: 93%
“…WGMs of the 47 S. aureus strains were obtained. The reliability, reproducibility, and accuracy of the experimentally derived WGMs were determined using a USA400 (MW2) and a USA300 (FPR3757) strain as previously described by our group (24). Essentially, this was done by comparing the XbaI in silico maps of MW2 and USA300 (FPR3757) to the corresponding experimentally derived WGMs, which were found to be nearly identical.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations